PENGARUH AKTIVITAS INDUSTRI TERHADAP PENINGKATAN EKONOMI PENDUDUK DAN PERKEMBANGAN PERDAGANGAN JASA DI KOTA BATAM - Boni Kasih Napitupulu; Prihadi Nugroho (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Indonesia as one of the developing country has some of coastal areas which utilized to develop the industrial activities based on manufacturing industry with labor intensive or even capital intensive.The development of industry activities in Batam are rely on domestic investment and foreign investment. One of the targeted region of industrial development is Batam City. With full support of industrial development from government on Economic Exclusive Zone, now industrial sector become the influence sector and leading sector in Gross Domestic Product of Batam City. It is also become the main focus of economic development. The aim of this research is to analyze and observe the influence of industrial activity to an increase in citizens’ economy based on income and the development of trade and services in Batam City. This research use quantitative approach with survey research method. The data collections are done with field surveys and questionnaires. Sampling which used in this research is purposive sampling, which targeted the sample according to the objective of research, therefore, the samples are the citizens who work in industrial sector. The study of this research shows that there are an increase in citizen’s economy and the development of trade and services as multiplier effect as the result of industrial activities in Batam City.